Global-in-Time Asymptotic Solutions to Kolmogorov-Feller-Type Parabolic Pseudodifferential Equations with Small Parameter—Forward- and Backward-in-Time Motion - V. G. Danilov (Abstract and Applied Analysis)
We discuss the construction of solutions to the inverse Cauchy problem by using characteristics.